KARAKTERISTIK POMPA SENTRIFUGAL ALIRAN CAMPUR DENGAN VARIABLE FREQUENCY DRIVE - Handayani, Sri Utami (ROTASI, 2013)
In an industry that uses large centrifugal pumps continuously, pump speed setting can reduce energy consumption significantly. By changing the speed of a centrifugal pump,Â  capacity, head, and pump power required will change according to pump affinity laws. Speed of a centrifugal pump can be changedÂ  by variable frequency drive . This study aimed to investigate the characteristics of mixed flow centrifugal pumps with variable frequency drive. The results showed that 10% of maximum speed reduction can decrease power consumtion until 50%, while the increase in the efficiency is maximum 7.2%. The power reduction is different for different speed reduction. In a dynamic head dominated system the efficiency will remain constant during speed reduction while in static head dominated system will change.